Psychoanalytic, Psychosocial, and Human Rights Perspectives on Enforced Disappearance (Taylor & Francis, 2024)
Disappearance, Luci, Torture, Enforced, Bianchi, Human, Psychoanalysis, Trauma, enforced, disappearance, psychoanalytic theory, disappearance, human
English
Keywords: Human rights, civil rights; Psychoanalytical and Freudian psychology; Psychology; Disappearance, Luci, Torture, Enforced, Bianchi, Human, Psychoanalysis, Trauma, enforced, disappearance, psychoanalytic theory, disappearance, human